TRAIT AND FACTOR THEORY ANALYSIS: LITERATURE REVIEW - Anna Ismawati; Mega Iswari; Daharnis (Literasi Nusantara, 2022)
The problem that is often experienced by students is that there are still many students who are confused about what their talents, interests or potential are. This study aims to provide an overview based on the literature on Trait and Factor theory that can be used as a career counseling approach to help students choose their future education or work by understanding the fit between themselves and their future work. This study uses a literature study which aims to examine more deeply about the themes raised. The results show that career maturity is quite important because it helps individuals make the right career choices.